X-ray Computed Tomography for Capillary Collapse of Loose Unsaturated Sand. (2016) - Moscariello, Mariagiovanna; Salager, Simon; Cuomo, Sabatino
Abstract: The collapse of unsaturated soils consists of the reduction in volume upon wetting at constant total stress. Several studies at the macro scale outline the influence of initial void ratio, confining pressure and matric suction on the onset of collapse of standard laboratory specimens. Conversely, few observations at the micro scale are available in the literature, although the influence of the particles arrangement and intergranular bonding has been formerly supposed. The collapse of fine sand derived by a pyroclastic soil of Southern Italy is investigated in this paper at the microscale using the X-ray Computed Tomography. The experimental procedure, formerly tested on similar pyroclastic soils, consists into testing a remoulded specimen (only loaded by its self-weight), which undergoes a reduction of matric suction until the collapse occurs. The laboratory investigation aims to: i) follow the transformation of the particles arrangement; ii) measure the global variations of the specimen in terms of water content, porosity and saturation degree during the wetting stage; iii) measure the local porosity, water content and saturation degree in several representative sub-volumes of the specimen. The experimental evidence outlines that the collapse occurs at very low suction while it is not mandatory to reach the complete saturation, emphasized by the presence of macro-voids at collapse.